Treatment of Hemorrhoids: actualización - Bermúdez, Jorge (Cirugía del Uruguay, 1981)
After a brief introduction in the ethiology and pathogeny of hemorrhoids, the different therapeutic procedures are presente.d. The ambulatory treatment is prefered in particular the inyection and banding. The author i